Penerapan Manajemen Risiko PT Bank Shinhan Indonesia Periode 2023-2024 - Nindy Angelita Eka Sahri Saban; Lita Melyani; Kornelia Lindahati Dakhi (Yayasan Al-Afif, 2025)
This study analyzes the implementation of risk management at PT Bank Shinhan Indonesia for the 2023–2024 period. The research focuses on credit risk, market risk, liquidity risk, operational risk, compliance risk, legal risk, reputation risk, and strategic risk. Data were obtained from audited financial statements and regulations issued by the Financial Services Authority (OJK) and Bank Indonesia. The results show that, although credit risk and operational risk increased in 2024, the bank remained within the safe limits set by regulators. Risk mitigation was strengthened through higher loan loss provisions and improved internal controls. The bank’s financial performance, compliance, and reputation remained stable, with an average quantitative risk indicator of 87.75. This study provides a comprehensive overview of risk management implementation in a national private bank, relevant to operational sustainability and stability.